PENGARUH KOMPETENSI, MOTIVASI DAN BUDAYA PERUSAHAAN TERHADAP KINERJA KARYAWAN PADA UPTD PUSKESMAS PURBOLINGGO LAMPUNG TIMUR - Titin Rosdyanti; Suwarto Suwarto (Derivatif : Jurnal Manajemen, 2020)
Position and role of Civil Servants as elements of the state apparatus is important tasked with carrying out services well. The form of service performance to the community is through efforts to provide health services to the communityespecially at the Health Center. Several factors related to employee performance are competency, motivation and organizational culture. The purpose of this study was to determine the effect of competence, motivation and organizational culture on employee performance at the UPTD Puskesmas Purbolinggo, East Lampung.The method used in this research is the explanatory survey method. This type of research is quantitative research with the object of research are competence, motivation, organizational culture and employee performance. The study population was employees at the Puskesmas Purbolinggo with a total sample of 52 respondents. Data collection techniques using questionnaires. The analytical tool used is to use data quality analysis and multiple linear regression analysis.The results showed that competency, motivation and organizational culture influence both partially and simultaneously on employee performance. Seeing the significance obtained, the most influential variable on employee performance is the organizational culture variable.Keywords: Competence, Motivation, Organizational Culture, Employee Performance